2014
DOI: 10.1501/vetfak_0000002606
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of severe combined immunodeficiency (SCID) disease of Arabian horses raised at the state stud farms in Turkey

Abstract: Summary:Severe Combined Immunodeficiency (SCID) is a lethal and autosomal recessive hereditary disorder, which has frequently been reported in Arabian horses, dogs, mice and humans. The genetic basis of equine SCID is 5-base pairs deletion in the DNA-dependent protein kinase catalytic subunit (DNA-PKcs) gene. Up to date, there is no information on the presence of SCID in Arabian horses reared in Turkey either by clinical observation or molecular diagnosis. The main aims of this study were to investigate the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…DNA sequencing was used to investigate the five-nucleotide deletion in the DNA-PKcs gene in Arabian horses reared on Eskişehir private farms. Cinar Kul et al [19] showed that there were no SCID genetic defects in Turkish Arabian horse populations in state breeding farms. Supporting the previous study, our research indicates that all samples obtained from the private horse farms of Eskisehir were normal in terms of SCID hereditary defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DNA sequencing was used to investigate the five-nucleotide deletion in the DNA-PKcs gene in Arabian horses reared on Eskişehir private farms. Cinar Kul et al [19] showed that there were no SCID genetic defects in Turkish Arabian horse populations in state breeding farms. Supporting the previous study, our research indicates that all samples obtained from the private horse farms of Eskisehir were normal in terms of SCID hereditary defects.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous genetic studies have investigated the five nucleotide deletion in the DNA-PKcs gene using primers that yield a PCR product of 521 bp [25], 259 bp [15], 235 bp [16], 179 bp [10], 174 bp [22], 169 bp [8,26], 163 bp [1,9,19,27], 162 bp [11], and 135 bp [13,17] in different Arabian horse populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were collected in a previous study [12] . Also positive control samples carrying the mutations were sent by Dr. Brooks and Dr. McCue, for LSF and PSSM-I diseases respectively.…”
Section: Animal Materialsmentioning
confidence: 99%